Media Sosial Sebagai Media Informasi Penataan Lighting Bagi Videografer: Studi Etnografi Virtual pada Akun Instagram @Fiqri_Fox (International Forum of Researchers and Lecturers, 2024)
This research reveals the crucial role of Instagram, particularly the @fiqri_fox account, in shaping a community of videographers who actively learn and share. Through a virtual ethnography approach, it is found that this account not only presents comprehensive lighting tutorials, but also creates an inclusive dialog space. Using the virtual ethnography method, this research explores in depth how the Instagram account @fiqri_fox becomes a reference for videographers in understanding lighting techniques. The results of this study highlight the great potential of social media, especially Instagram, as an effective learning tool. Accounts like @fiqri_fox have proven that with the right approach, the platform can bridge the gap between theory and practice.